'The players are the focus, it's never spoken about as coaches': perceived factors influencing the mental health of Australian elite-level coaches - Frost, J.; Purcell, R.; Rice, S. M.; Walton, C. C. (Psychology of Sport and Exercise, 2026)
Elite-level coaches operate within highly demanding, pressurised and unstable high-performance environments that can increase their risk of mental ill-health. This qualitative study investigated perceived factors influencing the mental health of Australian elite-level coaches using an ecological systems approach. Fourteen coaches (men = 12, women = 2) from a range of individual and team sports participated in a single semi-structured interview. Five overarching themes perceived to influence the mental health of Australian elite-level coaches were developed through reflexive thematic analysis, including: (1) encountering multifaceted demands, (2) using psychological resources to moderate the demands of coaching, (3) the protective value of interpersonal networks, (4) the influence of organisational expectations and support, and (5) stigma impedes mental health and help-seeking. Within an ecological systems framework, elite coaches primarily described encountering organisational stressors (e.g. job insecurity, poor work-life balance) that were managed by leveraging individual (e.g. psychological skills), interpersonal (e.g. robust social networks) and organisational (e.g. flourishing environments) supports. Coaches who were unable to employ effective coping strategies, engage with their support networks and lacked robust organisational supports (e.g. promoting a work-life balance) described feeling more vulnerable to poor mental health. The findings suggest that elite sports organisations should offer coaches opportunities to develop psychological skills (e.g. self-compassion), spend adequate time with their support network, and work in psychologically safe environments that promote flourishing. Longitudinal research is needed to identify which factors exert the greatest influence upon the mental health of elite coaches, enabling sports organisations to direct their resources to support coaches in a timely and effective manner.